Ciclo menstrual: avaliação de alterações hematológicas - Leticia Goncalves Freitas (2016)
Menstrual cycle progresses with cellular replication and growth under the influence of hormones, growth factors, neurotransmitters and regulatory molecules. Menstruation is part of a hemostatic process triggered by the formation of platelet aggregate and fibrin clot, fibrinolytic system activation, which dissolves the clot, and remodeling of endometrial tissue. P-selectin (CD62P) is a platelet surface glycoprotein which mediates interactions between the endothelium, platelets and leukocytes, playing an important role in the inflammation/thrombosis interaction. GPIIIa (CD61), GPIIb/IIIa (CD41a) and GPIX (CD42a) glycoproteins act in the adhesion and platelet aggregation process when blood vessel injury occurs. The interaction between platelets and leukocytes (PLA) constitutes an anchorage surface for inflammatory cells, apart from secreting various proteases that increase platelet adhesion. The elevated plasma levels of D-Di, PAI-1 and factor VIII, is associated with hypercoagulability and increased risk of venous thrombosis. In this way, the aim of this study was to investigate whether complete blood count (CBC), surface platelet markers, %APL and plasma levels of D-Di, PAI-1 and FVIII are able to clarify the hematological changes during menstruation and in the middle of menstrual cycle, as well as the influences of the use of combined oral contraceptives (OC) and age on this process. 46 women were evaluated, including young non-combined OC users (Young = 16), combined OCusers (Young-OC = 20) and climaterium non-combined OC users (Climaterium = 10). CBC was carried out semi-automatically, surface platelet markers and APL were analyzed by flow cytometry and coagulation and fibrinolysis markers by ELISA. Data obtained in this study allow us to conclude that neutrophil count, platelet activation and plasma levels of D-Di have variation depending on the menstrual cycle. Neutrophil count, platelet activation, %PNA, plasma levels of D-Di, and PAI-1 are influenced by the use of combined OC. Platelet count and PAI-1 serum levels are influenced by age of the woman. There are positive correlations among platelet count, platelet surface markers, PLA, coagulation cascade and fibrinolysis whose intensity depends on menstrual cycle phase, combined OC use and woman's age.